2015
DOI: 10.1007/s11096-015-0184-2
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs in paediatrics: caution with varicella!

Abstract: Anti-inflammatory drugs have been suspected on several occasions to have promoted development of bacterial infection among varicella patients. Some countries have not implemented childhood varicella vaccination. Three cases in our hospital suggested the predisposing role of NSAIDs in varicella patient deterioration. Open access to these drugs widely increases their use and patient information should be continually provided in the medical offices and at dispensing pharmacy counters. Taking account of the benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…This study indicates a strong association between the use of NSAIDs and severe NSTI, in particular in children with varicella [66]. In conclusion, it is worth being extremely cautious when prescribing ibuprofen to children with varicella because of the increased risk of complications [67]. …”
Section: Tolerability Profiles In Other Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study indicates a strong association between the use of NSAIDs and severe NSTI, in particular in children with varicella [66]. In conclusion, it is worth being extremely cautious when prescribing ibuprofen to children with varicella because of the increased risk of complications [67]. …”
Section: Tolerability Profiles In Other Conditionsmentioning
confidence: 99%
“…of patientsDisorderTreatmentAdverse events/risk2001Lesko SM [63]224VaricellaIbuprofen alone or with paracetamolGAS infections and necrosis of soft tissues2002Byington CL [64]540Varicella and pneumoniaIbuprofenEmpyema2008Mikaeloff Y [65]140,111VaricellaIbuprofen (and other NSAIDs)Cellulitis, abscess, fasciitis and necrosis2008Souyri C [66]266Varicella and other viral infectionsIbuprofen (and other NSAIDs)Serious necrotising soft-tissue infections2015Durand L [67]3VaricellaNSAIDs, including ibuprofenSuperinfectionPleurisy-pneumonia GAS group A streptococci, NSAIDs non-steroidal anti-inflammatory drugs …”
Section: Tolerability Profiles In Other Conditionsmentioning
confidence: 99%
“…This study indicates a strong association between the use of NSAIDs and severe NSTI, in particular in children with chickenpox [29]. As a consequence of these growing evidences, the use of ibuprofen for symptom control in chickenpox has been progressively abandoned [30,31].…”
Section: Chickenpoxmentioning
confidence: 81%
“…Although benign, varicella-associated complications are frequent. Studies have reported potential increase in risks and severe skin associated complications with the use of non-steroidal anti-inflammatory (NSAI), 2 , 3 however, without proved relationship with necrotizing fasciitis. 1 , 6 Exposure to ibuprofen compromises the leukocytosis function, promotes an increase of inflammatory cytokine production, 1 , 2 , 5 and creates a convenient environment for bacterial growth.…”
mentioning
confidence: 99%
“…Apesar de sua benignidade, as complicações da varicela são frequentes. Estudos têm demonstrado potencial aumento do risco de complicações cutâneas graves em associação ao uso de anti-inflamatórios não esteroides (AINEs), 2 , 3 sem, no entanto, relação comprovada com fasceíte necrotizante. 1 , 6 Pensa-se que a exposição ao ibuprofeno compromete a função leucocitária e promove aumento de produção de citocinas inflamatórias, 1 , 2 , 5 criando ambiente propício para crescimento bacteriano.…”
unclassified